2000
DOI: 10.1095/biolreprod63.1.274
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-Dependent Up-Regulation of Adipose Leptin Secretion In Vitro During Pregnancy in Mice1

Abstract: Circulating leptin levels are elevated during the later stages of pregnancy in mammals, suggesting that maternal leptin may play a role in maintenance of pregnancy and/or preparation for parturition and lactation. The regulation and source of circulating leptin during pregnancy remains undetermined, but leptin mRNA levels increase in adipose tissue during this time in some species. Considerable controversy exists whether placenta is also a leptin-secreting tissue during pregnancy. Here, we directly demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 47 publications
(82 reference statements)
3
38
0
Order By: Relevance
“…In contrast, some studies have failed to detect the presence of leptin in the rat placenta (8) and in rodents, unlike humans, the placenta may not be the major source of maternal leptin production (7). Indeed, in mice, hyperleptinaemia during pregnancy primarily results from corticosterone-dependent up-regulation of leptin secretion from adipose tissue (50). The present study demonstrated protein expression of leptin and ObR-S in the rat placenta near term (day 21, term is 23 days) and demonstrates that placental leptin expression is responsive to glucocorticoid status.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, some studies have failed to detect the presence of leptin in the rat placenta (8) and in rodents, unlike humans, the placenta may not be the major source of maternal leptin production (7). Indeed, in mice, hyperleptinaemia during pregnancy primarily results from corticosterone-dependent up-regulation of leptin secretion from adipose tissue (50). The present study demonstrated protein expression of leptin and ObR-S in the rat placenta near term (day 21, term is 23 days) and demonstrates that placental leptin expression is responsive to glucocorticoid status.…”
Section: Discussionsupporting
confidence: 54%
“…The plasma levels of leptin are highly correlated with adipose tissue mass and fall in both humans and mice after weight loss (Maffei et al, 1995). Kronfeld-Schor et al (2000) directly demonstrated that leptin secretion rates from mouse adipose tissue in vitro are decreased during early pregnancy and up-regulated during late pregnancy and lactation and these changes in leptin secretion rates in vitro paralleled those of circulating leptin in vivo during pregnancy. On the other hand, the increase in circulating leptin levels during mid to late pregnancy does not consistently correlate with adiposity in rats (Kawai et al, 1997;Amico et al, 1998), mice Tomimatsu et al, 1997), and humans (Butte et al, 1997).…”
Section: Expression Of Leptin Rna In the Adipose Tissue Of Non Pregnamentioning
confidence: 91%
“…One possible explanation for this is that adipose tissue continues to secrete leptin for a brief time after parturition (Kronfeld-Schor et al, 2000).…”
Section: Expression Of Leptin Rna In the Placenta During Pregnancy Inmentioning
confidence: 99%
“…Decreased leptin mRNA expression in visceral fat at D14 may limit placental soluble Ob-R mediated hyperleptinemia at the initiation of placental soluble Ob-R secretion in accordance with low fetal energy demands during early to middle gestation and the maternal body prepares for the elevated metabolic demands of late pregnancy and lactation. 9,35,36) At D17, leptin mRNA expression in visceral fat from ZnDF pregnant mice significantly decreased to 50% and that of placental soluble Ob-R mRNA and Ob-R protein decreased to 75% and 40% compared with that observed in control mice, respectively. In contrast, the expression of placental soluble Ob-R mRNA and Ob-R protein in ZnSP pregnant mice tended to increase to 120% and 140%, respectively, compared with that observed in control mice.…”
Section: Discussionmentioning
confidence: 95%
“…Tomimatsu et al suggested that plasma leptin concentrations dramatically rise from D10.5, peak during the third trimester of pregnancy, and rapidly decrease to non-pregnant levels during lactation. 9,35,36) These dramatic increases suggest that leptin may be particularly important during stages of fetal growth and development (late pregnancy) but less so during stages of organogenesis (early pregnancy). During pregnancy, leptin may act on the hypothalamus and regulate energy expenditure, neuroendocrine functions, glucose metabolism, and insulin sensitivity in dams.…”
Section: Discussionmentioning
confidence: 99%